Bullying Prevention with Strengthening Islamic Values in the Book of Adab ‘Alim Wa Muta’allim by Kyai Hasyim Asy’ari at MTs Ma’arif Pakis School Malang Regency - Izzuddin, Ahmad; Amrullah, Abdul Malik Karim (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The phenomenon of bullying in children is still rampant in society, especially in the school environment. Efforts to prevent bullying actions need to be made by various related parties. This service research aims to implement the Islamic paradigm and values in the Kitab Adab Alim wa Muta'allim by Kyai Hasyim Asy'ari as guidelines and ethical sources in efforts to prevent bullying, transform strategies that must be implemented and form an educational ecosystem in the Ma'arif education environment in Malang Regency. The method used in this research is Asset Based Community Development (ABCD). The result of this research is that the Islamic paradigm and values in the Book of Adab Alim wa Muta'allim by Kyai Hasyim Asy'ari should be a guideline and ethical source in efforts to prevent bullying in the Ma'arif education environment in Malang Regency because the values contained in the Book of Adab Alim wa Muta'allim are still very relevant to become an ethical foundation to prevent bullying in schools under Nahdlatul Ulama. The strategy that LP Ma'arif Malang Regency can implement to habituate child-friendly schools with the Islamic paradigm and values in the Kitab Adab Alim wa Muta'allim Kyai Hasyim Asy'ari is to use the AGIL scheme, which stands for adaption, goal attainment, integration and latency. Schools under LP Ma'arif Malang Regency can be initiators and pioneers of child-friendly and anti-bullying schools with the Islamic paradigm and values in the Book of Adab Alim wa Muta'allim Kyai Hasyim Asy'ari.